2021
DOI: 10.1007/s00394-021-02527-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary approaches to stop hypertension (DASH) diet on attention-deficit hyperactivity disorder (ADHD) symptoms: a randomized controlled clinical trial

Abstract: Background The dietary approaches to stop hypertension (DASH) diet has several components that might improve attention deficit hyperactivity disorder (ADHD) symptoms. This randomized controlled clinical trial (RCT) aimed to investigate the effect of the DASH diet on ADHD symptoms in children, for the first time.Methods Children (aged 6-12 years) with ADHD were randomized to receive a DASH or a control diet for 12 weeks. The severity of ADHD symptoms [determined by abbreviated 10-item Conner's scale (ACS), 18-i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…In conclusion, dietary patterns seem to play a potential role in the risk of ADHD, as patterns described as “Junk-food”, “Processed”, “Snack”, “Sweet”, and “Western-like” are the ones most positively associated with this pathology [ 5 , 6 , 8 ], whereas healthy eating patterns, such as the Mediterranean diet, are inversely associated with ADHD [ 7 , 9 ]. These data support the idea that not only specific nutrients or chemical food compounds but the whole diet should be considered in ADHD.…”
Section: Dietary Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, dietary patterns seem to play a potential role in the risk of ADHD, as patterns described as “Junk-food”, “Processed”, “Snack”, “Sweet”, and “Western-like” are the ones most positively associated with this pathology [ 5 , 6 , 8 ], whereas healthy eating patterns, such as the Mediterranean diet, are inversely associated with ADHD [ 7 , 9 ]. These data support the idea that not only specific nutrients or chemical food compounds but the whole diet should be considered in ADHD.…”
Section: Dietary Patternsmentioning
confidence: 99%
“…The dietary approach to stop hypertension (DASH) is a well-known healthy eating pattern, which is characterized by high amounts of fruits, vegetables, low-fat dairy products, vitamin C, and low amounts of simple sugars. In a 12-week randomized controlled clinical trial in Iran [ 9 ], this dietary pattern appears to improve ADHD symptoms, measured by the Abbreviated Conners Scale (ACS), the 18-item Swanson, Nolan, and Pelham scale (SNAP-IV), and the Strengths and Difficulties Questionnaire (SDQ). Although there is only one study with DASH in ADHD, it is reasonable to think it could be beneficial to these patients because of its known health benefits [ 93 , 94 , 95 , 96 , 97 , 98 , 99 ].…”
Section: Nutritional and Dietary Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a vegetarian dietary pattern rich in all types of vegetables, fruits, beans, and grains was negatively associated with ADHD [ 20 , 21 ]. Other dietary patterns rich in polyphenols, such as the Mediterranean diet and the Dash diet, were negatively correlated with ADHD and improved ADHD symptoms [ 22 , 23 ]. A cross-sectional study showed that low adherence to the Mediterranean diet may contribute to the development of ADHD [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several components of the dietary approaches to stop hypertension diet, such as high amounts of fruits, vegetables, low-fat dairy products, and vitamin C and low amounts of simple sugars, have been suggested to improve ADHD symptoms. A randomized controlled trial investigated the effect of this diet administered for 12 weeks to 80 children with ADHD aged 6 to 12 years [ 68 ]. Following adjustment for confounders, various measures determined by the abbreviated 10-item Conners’ scale, 18-item Swanson, Nolan and Pelham scale and the strengths and difficulties questionnaire, parent-, teacher- and child-reported hyperactivity, emotional symptoms, teacher-reported conduct problems, peer relationship problems, and prosocial behaviors were significantly improved in the dietary approaches to stop hypertension group compared to the control group [ 68 ].…”
Section: Dietary Patternsmentioning
confidence: 99%